Environmental ethics and animal welfare: rural development strategy in peace - "education for peace” (Revista Sistemas de Producción Agroecológicos, 2019)
The education for peace program is one of the tools used by the National Government who, under the Ministry of Education, makes the inter-administrative agreement No. 0833 of 2018 with the Universidad de los Llanos for the implementation of strategies that allow the community of municipalities affected by the war, the adequate use of natural resources in a sustainable manner. Said program articulates the individual's own abilities and their manifestation on the conservation of the natural wealth characteristic of the ecosystems of the region. For the implementation and execution of the Education for Peace program for sustainable rural development, fifty people are linked among children, youth, peasants, women, Afro-descendants and victims, from the municipalities of El Dorado and Granada in the department of Meta. The general objective of this work is to promote environmental ethics and animal welfare as a strategy for rural development in peace and for this the methodology is implemented through guided practical theoretical workshops on personal development, leadership, active listening, expression, communication and management. of own change, folkloric cultural sensitization and Human and Family Rights, behaviors are implemented as part of the process of building a stable and lasting peace. Sensitizing and providing tools allows communities to know and lead themselves to take on new challenges. Another of the activities developed is based on maintaining the equilibrium of natural ecosystems through the sighting of birds that, in addition to generating knowledge, is an instrument for implementing work through the development of ecological tourism. This project is part of the principles of cultural recognition and the region's own identity.
Keywords: education; post-conflict; peace